‘Boghossian’s Blind Reasoning’, Conditionalization, and Thick Concepts. A Functional Model - Ramírez, Olga (ETHICS IN PROGRESS, 2012)
Boghossian’s (2003) proposal to conditionalize concepts as a way to secure their legitimacy in disputable cases applies well, not just to pejoratives – on whose account Boghossian first proposed it – but also to thick ethical concepts. It actually has important advantages when dealing with some worries raised by the application of thick ethical terms, and the truth and facticity of corresponding statements. In this paper, I will try to show, however, that thick ethical concepts present a specific case, whose analysis requires a somewhat different reconstruction from that which Boghossian offers. A proper account of thick ethical concepts should be able to explain how ‘evaluated’ and ‘evaluation’ are connected.